2023
DOI: 10.3390/microorganisms11102370
|View full text |Cite
|
Sign up to set email alerts
|

Genetic- and Fiber-Diet-Mediated Changes in Antibiotic Resistance Genes in Pig Colon Contents and Feces and Their Driving Factors

Tao Wang,
Yuheng Luo,
Xiangfeng Kong
et al.

Abstract: Comprehensive studies on the effects of genetics and fiber diets on antibiotic resistance genes (ARGs) remain scarce. In this study, we analyzed the profiles of ARGs in colonic contents and fecal samples of Taoyuan, Duroc, and Xiangcun pigs (n = 10) fed at different fiber levels. Through macrogenomic analysis, we identified a total of 850 unique types of ARGs and classified them into 111 drug resistance classes. The abundance of partially drug-resistant ARGs was higher in the colonic contents of local pig bree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The results showed that high fiber diets significantly reduced the normalized abundance of total VFs in swine feces, and there was no significant difference in the abundance of VFs between breeds ( Figures 6A , C ). Previous laboratory studies have shown that high-fiber diets resulted in a significant reduction in the normalized abundance of the integrase gene intI1 in feces ( 19 ). After examining the amount of SCFAs in feces we found that the high fiber diet significantly elevated the amount of total SCFAs in swine feces, but there were no differences between breeds ( Figure 6B ).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that high fiber diets significantly reduced the normalized abundance of total VFs in swine feces, and there was no significant difference in the abundance of VFs between breeds ( Figures 6A , C ). Previous laboratory studies have shown that high-fiber diets resulted in a significant reduction in the normalized abundance of the integrase gene intI1 in feces ( 19 ). After examining the amount of SCFAs in feces we found that the high fiber diet significantly elevated the amount of total SCFAs in swine feces, but there were no differences between breeds ( Figure 6B ).…”
Section: Resultsmentioning
confidence: 99%
“…Several factors contribute to the spread of ARGs in various environments. Intracellular ARGs (iARGs) are prominent in nutrient-rich environments, while extracellular ARGs (eARGs) are prevalent in aquatic environments [ 64 ]. eARGs can be adsorbed by soil and sediment particles, avoiding DNase degradation and persisting longer than iARGs.…”
Section: Types Of Args In Aquatic Environmentmentioning
confidence: 99%